Testing the consistency of three-point halo clustering in Fourier and configuration space. Issue 1 (24th January 2018) - Hoffmann, K; Gaztañaga, E; Scoccimarro, R; Crocce, M
Abstract: We compare reduced three-point correlations Q of matter, haloes (as proxies for galaxies) and their cross-correlations, measured in a total simulated volume of ∼100 ( h −1  Gpc) 3, to predictions from leading order perturbation theory on a large range of scales in configuration space. Predictions for haloes are based on the non-local bias model, employing linear ( b 1 ) and non-linear ( c 2, g 2 ) bias parameters, which have been constrained previously from the bispectrum in Fourier space. We also study predictions from two other bias models, one local ( g 2  = 0) and one in which c 2 and g 2 are determined by b 1 via approximately universal relations. Overall, measurements and predictions agree when Q is derived for triangles with ( r 1 r 2 r 3 ) 1/3 ≳60  h −1  Mpc, where r 1 − 3 are the sizes of the triangle legs. Predictions for Q matter, based on the linear power spectrum, show significant deviations from the measurements at the BAO scale (given our small measurement errors), which strongly decrease when adding a damping term or using the non-linear power spectrum, as expected. Predictions for Q halo agree best with measurements at large scales when considering non-local contributions. The universal bias model works well for haloes and might therefore be also useful for tightening constraints on b 1 from Q in galaxy surveys. Such constraints are independent of the amplitude of matter density fluctuation (σ8 ) and hence break the degeneracy between b 1 and σ8, present in galaxy two-point correlations.